A causal analysis of time-varying speed camera safety effects based on the propensity score method. (December 2020) - Li, Haojie; Zhang, Yingheng; Ren, Gang
Highlights: We evaluate the time-varying safety effects of speed cameras. Speed cameras have significantly reduced the number of road accidents. Safety effects of speed cameras experienced a sharp decrease after the installation. Appropriate management is important to maintain the effectiveness of speed cameras. Abstract: Introduction: Speed limit enforcement cameras provide an effective approach to reduce vehicle speeds and the number of road accidents. However, it is still unclear whether the safety effects of speed cameras show durability over long periods of time. This paper analyses how the effects of speed cameras on road accidents change over time. A total number of 771 camera sites and 4787 potential control sites are observed for a period of 18 years (1999–2016) across England. Method : Covariates such as road class, crash history, speed limit, and annual average daily traffic (AADT) are included in the data set. A difference in difference (DID) based propensity score matching (PSM) method is employed to select proper control sites and estimate the treatment effects. The safety effects of speed cameras are then evaluated from a long-term perspective. The post-treatment period is divided into four equal-length periods: early, medium 1 and 2, and late. Results and Conclusions : The results show that speed cameras have significantly reduced the number of road accidents near the camera sites. However, the effects vary across different time periods. The safety effects of speed cameras experienced a sharp decrease during the medium periods after an initial period of highly reduced accidents (medium 1: −53.1%, medium 2: −40.7%) and recovered slightly during the late period. In addition, to evaluate the criteria for selecting camera sites in the UK, we further investigated whether speed cameras at high risk sites have better safety performance. The results show that while safety effects at high risk camera sites also decreased during the medium periods, the reduction was smaller (medium 1: −20.8%, medium 2: −2.1%). Practical Applications : Appropriate road traffic regulations and management, as well as proper camera sites selection criterion, are important to maintain the effectiveness of speed cameras.